2022
DOI: 10.36418/edv.v2i4.412
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Affecting Regional Financial Independence in the Framework of a Policy Strategy For Increasing Regional Original Income

Abstract: The regional autonomy policy, which is accompanied by the provision of balancing funds, has a goal, one of which is to have an impact on the financial independence of regency/municipal governments in Indonesia. The balancing funds provided should have an effect or have an impact on regional financial independence. This research is directed to see to what extent the relationship of fiscal decentralization can provide an increase in regional financial independence. Based on the results of the panel data regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The results showed that, in comparison to other regions, the average economic growth is significantly larger. For instance, there have been numerous land conversions from non-industrial to industrial regions in the Serengan region [3].…”
Section: Preliminarymentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that, in comparison to other regions, the average economic growth is significantly larger. For instance, there have been numerous land conversions from non-industrial to industrial regions in the Serengan region [3].…”
Section: Preliminarymentioning
confidence: 99%
“…Economic growth is the change or expansion of the gross domestic product over a specific year. The process of increasing local economies' output of goods and services is the foundation for economic growth [3].…”
Section: Definition Of Leading Sectormentioning
confidence: 99%